The Effect Of Business Size, Business Age, And Education Level on the Use of Accounting Information (among MSMEs in the food sector, Cisewu District, Garut Regency - Shelvianti Chyntia Mutiara; Santi Damayanti (eCo-Buss, 2024)
Assessing the impact of factors such as age is the aim of this study, size, and level of education have from the utilisation of accountancy data in micros, small, and medium enterprises (MSMEs) operating in the food processing industry in Cisewu County, which is categorised as Ghartout District. In particular, the study will concentrate on the utilisation of accounting data in micro, small, and medium-sized enterprises (MSMEs). The data collection process for thats study is carried out using a methodical approach. For the purpose of analysing the data this is was collected and determining the importance on the findings, quantitative data analysis methods have been utilised. These tools include statistical tests. All micro, little, and medium companies (MSMEs) that are especially active in the food processing sector in Cisewu District, which is located in Ghartout Regency, are included in the scope of the study. A census of the complete population, which comprised of 62 different business units, was carried out by the research organisation in order to guarantee that the study would be accurate and comprehensive. In addition, the t-test and the F-test were utilised in order word determine the statistical to significance of the components that were linked with the utilisation of accounting information. Specifically, the results showed that the use of accountancy information by Micro, SME and Medium sized Enterprises (MSMEs) in the food industry in Cisewu District, Garut Regency was significantly and positively influenced by firm size, firm age and firm education level. This was the case in Cisewu District.